Inter-State Communications and Human Rights : Developments and Prospects - Garciandia, Rosana,; Gauci, Jean-Pierre, (Human Rights and Humanitarian Law E-Books Online, Collection 2025., 2025)
Developments at the international level over the past 5 years have re-ignited the relevance of a mechanism that had remained dormant for decades: inter-state communications before UN treaty bodies. Under-utilised and, consequently, under-studied, inter-state communications allow States to bring cases against other States for violations of their human rights obligations. Given the strong human rights dimension of cases currently under consideration by the ICJ and other international disputes, as well as the numerous and significant cases being presently considered by human rights treaty bodies and other human rights courts, this edited volume seeks to consider the potential of inter-state communications for promoting and ensuring respect for human rights around the globe.